Dynamic Properties and Energy Dissipation Study of Sandwich Viscoelastic Damper Considering Temperature Influence - Yeshou Xu; Zhaodong Xu; Yingqing Guo; Xinghuai Huang; Yaorong Dong; Qiangqiang Li (Buildings, 2021)
Viscoelastic dampers are a kind of classical passive energy dissipation and vibration control devices which are widely utilized in engineering fields. The mechanical properties and energy dissipation capacity of the viscoelastic damper are significantly affected by ambient temperature. In this work, dynamic properties tests of the sandwich type viscoelastic damper at different environmental temperatures are carried out. The equivalent fractional Kelvin model which can characterize the mechanical behavior of the viscoelastic damper with varying frequencies and temperatures is introduced to describe the dynamic properties and energy dissipation capability of the sandwich viscoelastic damper. The self-heating phenomenon of the sandwich viscoelastic damper is studied with a numerical simulation, and the dynamic properties and energy dissipation variation of the viscoelastic damper with self-heating processes are also analyzed. The results show that the dynamic properties of the viscoelastic damper are significantly affected by temperature, excitation frequency and the internal self-generated heating.